Quality of newborn care: adherence to guidelines for parenteral nutrition in preterm infants in four European countries. Issue 9 (18th September 2013) - Lapillonne, Alexandre; Carnielli, Virgilio Paolo; Embleton, Nicholas David; Mihatsch, Walter
Abstract : Objective: The level of adherence to guidelines should be explored particularly in preterm infants for whom poor nutrition has major effects on outcomes in later life. The objective was to evaluate compliance to international guidelines for parenteral nutrition (PN) in preterm infants across neonatal intensive care units (NICUs) of four European countries. Design: Clinical practice survey by means of a questionnaire addressing routine PN protocols, awareness and implementation of guidelines. Setting: NICUs in the UK, Italy, Germany and France. Participants: One senior physician per unit; 199 units which represent 74% of the NICUs of the four countries. Primary outcome measure: Adherence of unit protocol to international guidelines. Secondary outcome measure: Factors that influence adherence to guidelines. Results: 80% of the respondents stated that they were aware of some PN clinical practice guidelines. For amino acid infusion (AA), 63% of the respondents aimed to initiate AA on D0, 38% aimed to administer an initial dose ≥1.5 g/kg/day and 91% aimed for a target dose of 3 or 4 g/kg/day, as recommended. For parenteral lipids, 90% of the respondents aimed to initiate parenteral lipids during the first 3 days of life, 39% aimed to use an initial dose ≥1.0 g/kg/day and 76% defined the target dose as 3–4 g/kg/day, as recommended. Significant variations in PN protocols were observed among countries, but the type of hospital or the number of admissions per year had only a marginal impact on the PN protocols. Conclusions: Most respondents indicated that their clinical practice was based on common guidelines. However, the initiation of PN is frequently not compliant with current recommendations, with the main differences being observed during the first days of life. Continuous education focusing on PN practice is needed, and greater efforts are required to disseminate and implement international guidelines.